Opis samoglasnikov slovenskega knjižnega jezika z vidika spola govorečega - Tivadar, Hotimir (Slavistična revija, 2019)
The question of speakers' gender, as observed by their voices, was not dealt with in Toporisic's grammar (1976-) or in the Slovenski pravopis (Slovene orthography 2001). Research into vowels, which is based on material with systematically gender balanced distribution, begins in the 21st century, when consideration of both female and male speakers in the material becomes a linguistic standard and a necessity in phonetic-phonological scientific research. In this article, I also analyze F0 (basic tone), which defines speakers' gender, from a phonological point of view.
Keywords: fonetika; fonologija; gender; govor; phonetics; phonology; Slovenian language; Slovenian society; slovenska družba; slovenščina; speech; spol